1986
DOI: 10.1002/ajpa.1330710206
|View full text |Cite
|
Sign up to set email alerts
|

Morphometrics of the anterior dentition in strepsirhine primates

Abstract: Size variations in the anterior dentition were analyzed for 26 species of strepsirhine primates. The upper and lower incisor rows of strepsirhines, like those of anthropoid primates, scale isometrically with body size. Within the order Primates, strepsirhines exhibit the smallest incisors relative to body size, followed in increasing size by tarsiers, platyrrhines, and catarrhines. If the lateral teeth of the indriid toothcomb are interpreted as incisors and not canines, correlations between mandibular tooth s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…after Masters and Brothers 2002). However, Eaglen (1986) found no trends in morphological adaptations in the toothcombs of any of these taxa that reflect exudate acquisition.…”
mentioning
confidence: 52%
See 3 more Smart Citations
“…after Masters and Brothers 2002). However, Eaglen (1986) found no trends in morphological adaptations in the toothcombs of any of these taxa that reflect exudate acquisition.…”
mentioning
confidence: 52%
“…senegalensis feeding behavior have provided evidence that they use their toothcombs in some fashion to access exudates (Bearder and Martin 1980). Charles-Dominique (1977) and Eaglen (1986) observed that E. elegantulus and O. crassicaudatus have relatively narrow and high toothcombs compared with galagos that do not intensively exploit exudates. If exudativorous galagos are using the toothcomb to acquire difficult-to-reach exudates by using a high, narrow toothcomb, we predict that this morphological dental signal would be seen in a large sample of galago exudate feeders.…”
Section: Galago Dietsmentioning
confidence: 96%
See 2 more Smart Citations
“…It is also generally accepted that the specialized gummivores Euoticus and Phaner have distinctive tooth-scrapers. However, the association between tooth-scraper dimensions and exudativory is not particularly strong when seen across strepsirrhines generally (Eaglen 1986). Moreover, comparison of specialized exudativores, moderate exudativores and nonexudativores among galagids provides only limited support for a connection between tooth-scraper dimensions and exudativory (Burrows and Nash, Chap.…”
Section: Forewordmentioning
confidence: 99%